Contemporary Perspectives on Ageism (International Perspectives on Aging,, 2018)
This open access book provides a comprehensive European perspective on the concept of ageism, its origins, the manifestation and consequences of ageism, as well as ways to respond to and research ageism. The book represents a collaborative effort of researchers from over 20 countries and a variety of disciplines, including, psychology, sociology, gerontology, geriatrics, pharmacology, law, geography, design, engineering, policy and media studies. The contributors have collaborated to produce a truly stimulating and educating book on ageism which brings a clear overview of the state of the art in the field. The book serves as a catalyst to generate research, policy and public interest in the field of ageism and to reconstruct the image of old age and will be of interest to researchers and students in gerontology and geriatrics. This book is open access under a CC BY 4.0 license.